The broadening spectrum of spindle cell lipoma and related tumors: A review - Anders Meyer (Elsevier, 2022)
Spindle cell/pleomorphic lipoma has a wide range of histologic appearances and frequently presents diagnostic difficulties. All but the most common cases can be easily confused for locally aggressive or malignant entities. Recently, a family of related tumors resembling SCPL but with unusual clinical features and an atypical and aggressive histologic appearance has been described under the umbrella term of atypical spindle cell pleomorphic lipomatous tumors (ASCPLT). Proper identification of these tumors is critical to prevent unwarranted aggressive surgical and medical therapy. This review focuses on the clinical and histopathologic features of SCL and ASCPLT as well as the challenging differential diagnoses these tumors present.